STUDENTS' PERCEPTIONS OF THE SUGGESTOPEDIA LEARNING METHOD IN IMPROVING SPEAKING SKILLS FOR DELIVERING RECOUNT TEXTS - Fuad Durrotunnisa'; Muhammad Sukirlan; Mahpul Mahpul (Universitas PGRI Sumatera Barat, 2025)
This study aims to investigate students' perceptions of the Suggestopedia method in improving speaking skills, particularly in delivering recount texts. Suggestopedia is a language teaching method that emphasizes psychological comfort, relaxation, and enjoyment in the learning process through the use of music, games, and imaginative activities. The research employed a descriptive quantitative approach with a survey design involving 36 tenth-grade students from a Islamic Senior High School (MAN) in Bandar Lampung who had experienced learning through the Suggestopedia method. Data were collected through a closed-ended questionnaire using a 5-point Likert scale and semi-structured interviews to triangulate the findings. Quantitative data were analyzed descriptively, while qualitative data were thematically interpreted. The findings revealed that students generally had positive perceptions of the method, with high average scores across all measured aspects: awareness (79.7%), past experience (82.3%), knowledge (82.4%), motivation (83.3%), and social interaction (82.1%). These results indicate that Suggestopedia was well-received, especially in boosting students’ enthusiasm and participation in speaking activities. Interview data supported these findings, highlighting increased comfort, self-confidence, and creativity in expressing personal experiences. The study concludes that Suggestopedia effectively fosters a relaxed and supportive learning environment, which reduces anxiety and encourages spontaneous speaking. However, its successful implementation requires teacher readiness and sensitivity to different learner preferences. Suggestopedia proves to be a promising alternative method for improving students’ speaking fluency and confidence in recount text delivery.